EP541 Nationwide introduction of robotic minimally invasive surgery was associated with improved survival and decreased odds of severe complications in women with early-stage endometrial cancer: a population-based prospective cohort study. (1st November 2019) - Joergensen, S; Mogensen, O; Wu, CS; Lund, K; Iachina, M; Korsholm, M; Jensen, PT
Abstract : Introduction/Background: The oncological safety of minimally invasive techniques versus open access surgery in gynecological cancer is currently debated. Substantial changes in the surgical management of endometrial cancer necessitates evaluation to ensure survival is not compromised and the risk of severe complications is not increased. Methodology: A nationwide prospective cohort of all women with early-stage endometrial cancer who underwent surgery between January 1, 2005 and June 30, 2015 were retrieved from the Danish Gynecological Cancer Database. Data were linked with nationwide registers on socioeconomic status, deaths, hospital diagnoses and treatment using each woman´s civil registration number. The cohort was divided according to the time they underwent surgery; group 1 underwent surgery before the introduction of robotic minimally invasive surgery (RMIS) in their respective region, and group 2 underwent surgery after. Women in group 2 were subdivided in total abdominal hysterectomy (TAH), laparoscopic minimally invasive surgery (LMIS), and RMIS. Severe complications encompassed death within 30 days, intraoperative complications, and postoperative complications diagnosed within 90 days. Five-year overall survival was compared by multivariate Cox proportional hazards models stratified by histopathological risk. Odds of severe complications were compared by multivariate logistic regression. Results: A total of 5654 women were included. Women in group 1 (n=3091) had significantly higher mortality and odds of severe complications compared with women in group 2 (n=2563; hazard ratio [HR], 1.22; 95%confidence interval [CI], 1.05–1.42 and odds-ratio [OR], 1.39; 95% CI, 1.11–1.74, respectively). In group 2, TAH was associated with higher mortality and increased odds of complications compared with RMIS in adjusted analyses (HR, 1.70; 95%CI 1.31–2.19 and OR, 3.87; 95% CI, 2.52–5.93, respectively). Conclusion: The national introduction of RMIS transitioned the surgical approach for early-stage endometrial cancer towards minimally invasive surgery. This change was associated with improved survival and significantly reduced odds of severe complications. Disclosure: Nothing to disclose.